2021
DOI: 10.1155/2021/6666086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors and Outcomes Associated with Acute Kidney Injury in Patients Hospitalized for COVID-19: A Comparative Study between Diabetic and Nondiabetic Patients

Abstract: Background. The risk factors for acute kidney injury (AKI) development in patients with diabetes hospitalized for COVID-19 have not been fully studied yet. In this study, we aimed to estimate the rate of AKI among the hospitalized population with COVID-19 and to identify the risk factors associated with AKI among patients with diabetes. Material and Methods. This retrospective cohort study included 254 patients (127 with diabetes and 127 without diabetes) who were admitted for COVID-19 to a tertiary hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Among our study population, we observed an incidence of AKI of 25.8% similar to other reports [11,[22][23][24]. The reported rates of AKI are extremely variable; however, available evidence suggests that it likely affects >20% of hospitalized patients and >50% of patients in the ICU [25].…”
Section: Cumsupporting
confidence: 88%
See 1 more Smart Citation
“…Among our study population, we observed an incidence of AKI of 25.8% similar to other reports [11,[22][23][24]. The reported rates of AKI are extremely variable; however, available evidence suggests that it likely affects >20% of hospitalized patients and >50% of patients in the ICU [25].…”
Section: Cumsupporting
confidence: 88%
“…On the basis of our multivariate logistic regression analysis; higher leukocytes, decreased eGFR and presence of proteinuria were independent predictors of AKI. As reported previously, we observed a high prevalence of hematuria and proteinuria in COVID-19 patients with AKI [3,12,19,21,22]. However, in a recent study, they found no significant differences in proteinuria, hematuria and leukocyturia among patients with AKI compared with non-AKI patients [24].…”
Section: Cumsupporting
confidence: 68%
“…These data are critical for understanding disease onset and progression. Identifying the potential risk factors for AKI in individuals with coexisting COVID-19 should help to guide therapeutic methods and, as a result, improve the prognosis of these patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In present study, DM came out to be a significant risk factor for developing AKI as reported by other studies. 10,13,15 In a study by Khalili et al 18 , amongst hospitalized COVID-19 patients, AKI developed more in diabetics as compared to non-diabetics (62% vs. 38%). Hyperglycemia, suppressed immunity, thromboembolic events and sepsis/septic shock are important pathogenic mechanisms involved in causing AKI in DM.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%